Association between terminal pleural elastance and radiographic lung re-expansion after therapeutic thoracentesis in patients with symptomatic pleural effusion: a post-hoc analysis of a randomised trial. Issue 7 (12th July 2022) - Lester, Michael; Maldonado, Fabien; Rickman, Otis B; Roller, Lance J; Avasarala, Sameer K; Katsis, James M; Lentz, Robert J
Abstract : Objectives: Recurrent symptomatic effusions can be durably managed with pleurodesis or placement of indwelling pleural catheters. Recent pleurodesis trials have largely relied on lung re-expansion on post-thoracentesis radiograph as an inclusion criterion rather than pleural elastance as determined by manometry, which is an important predictor of successful pleurodesis. We investigated the association between lung re-expansion on post-pleural drainage chest imaging and pleural physiology, with particular attention to pleural elastance over the final 200 mL aspirated. Design: Post-hoc analysis of a recent randomised trial. Setting and participants: Post-results analysis of 61 subjects at least 18 years old with symptomatic pleural effusions estimated to be at least of 0.5 L in volume allocated to manometry-guided therapeutic thoracentesis in a recent randomised trial conducted at two major university hospitals in the USA. Primary outcome measures: The primary outcome was concordance of radiographic with normal terminal pleural elastance over the final 200 mL aspirated. We label this terminal elastance 'visceral pleural recoil', or the tendency of the maximally expanded lung to withdraw from the chest wall. Results: Post-thoracentesis chest radiograph and thoracic ultrasound indicated successful lung re-expansion in 69% and 56% of cases, respectively. Despite successful radiographic lung re-expansion, visceral pleural recoil was abnormal in 71% of subjects expandable by radiograph and 77% expandable by ultrasound. The sensitivity and positive predictive value of radiographic lung re-expansion for normal visceral pleural recoil were 44% and 24%, respectively. Conclusion: Radiographic lung re-expansion by post-thoracentesis chest radiograph or thoracic ultrasound is a poor surrogate for normal terminal pleural elastance. Clinical management of patients with recurrent symptomatic pleural effusions guided by manometry rather than post-thoracentesis imaging might produce better outcomes, which should be investigated by future clinical trials. Trial registration number: NCT02677883 ; Post-results.